2018
DOI: 10.1111/1467-8454.12139
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of the real effective exchange rates in high and upper‐middle income countries

Abstract: JEL codes: F31, F41, O47, O57 This paper revisits the nexus between real effective exchange rate (REER) and total factor productivity (TFP) by controlling for trade openness, financial development and natural resources rents. We use a sample of 60 highincome and upper-middle income countries over the period 1995-2015 and employ the GMM estimation framework. Our results advance the empirical knowledge on the drivers of REER by providing robust evidence that the impact of TFP is not uniform across different coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
7
0
3
Order By: Relevance
“…Using the case of high income and upper middle income economies Vogiazas et al (2019) confirmed that financial development and natural resources rents have no significant effect on the real effective exchange rates of the upper-middle income countries but this link is substantial for the high-income countries. Likewise, trade openness is the key factor that influences the exchange rates and the impact of total factor productivity varies for both countries.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Using the case of high income and upper middle income economies Vogiazas et al (2019) confirmed that financial development and natural resources rents have no significant effect on the real effective exchange rates of the upper-middle income countries but this link is substantial for the high-income countries. Likewise, trade openness is the key factor that influences the exchange rates and the impact of total factor productivity varies for both countries.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Berdasarkan penelitian Vogiazas et al (2019), keterbukaan perdagangan adalah persentase jumlah ekspor dan impor dalam PDB. Keterbukaan perdagangan mengindikasikan interaksi ekonomi suatu negara secara global dengan negara-negara lain.…”
Section: Hubungan Antara Keterbukaan Perdagangan Dan Nilai Tukarunclassified
“…The current debate on the financegrowth nexus has spawned a whole new empirical research that purports to shed additional light on the extant relationship between financial sector development and economic growth (see Aghion and Howitt 2009). For Vogiazas et al (2018) however, the existing evidence on the empirical relationship between financial sector development and economic growth remains, to a certain extent, inconclusive. Bagehot (1873) and Schumpeter (1911) were potentially two of the first academics to provide insightful arguments on the implications of the relationship between finance and growth.…”
Section: Banking Sector Development Determinantsmentioning
confidence: 99%